Foodborne botulism from consumption of homemade spoiled eggs: a case series and literature review - Wei, Suyu; Sun, Liang (Frontiers in Medicine, 2025)
Botulism is a rare but life-threatening condition that primarily results from ingestion of food contaminated with the exotoxins produced by Clostridium botulinum. Although uncommon in clinical settings, it is characterized by acute onset, severe manifestations, and a high mortality rate. Outbreaks linked to egg consumption are rarely reported, and cases occurring during pregnancy are even less common, posing unique diagnostic and therapeutic challenges. We report a family cluster of botulism in China that was associated with the consumption of homemade fermented eggs. All affected individuals exhibited symptoms indicative of botulism, including vomiting, dysphagia, restricted eye movement, progressive limb muscle weakness, and other neurological deficits. Electromyography revealed evidence of neuromuscular dysfunction, and laboratory testing confirmed the presence of C. botulinum type A toxin, establishing the diagnosis of foodborne botulism. Both patients received timely supportive care, with one case requiring management during pregnancy. Antitoxin therapy was not administered due to delayed recognition, but both patients recovered fully and were discharged without complications. The pregnant woman subsequently delivered without adverse maternal or neonatal outcomes, and no recurrence was observed during follow-up. Accurate diagnosis of botulism can be challenging and careful epidemiological assessment combined with laboratory confirmation is essential to properly identify and define these cases. These cases underscore the importance of early recognition, timely diagnosis, and prompt treatment in improving patient outcomes, particularly in pregnancy-associated botulism.